Effectiveness of Using Interactive Powerpoint Media on Chemical Bonding Material to Improve Student Learning Outcomes - Rosanna, Desi Lisa (LAVOISIER: Chemistry Education Journal, 2024)
Along with the development of Science and Technology (IPTEK), current educators and students need to improve the quality of education to be able to compete. Therefore, learning media is needed that can increase understanding by using interactive power points . The research aims to test the effectiveness of using powerpoint learning media on chemical bond material to improve the learning outcomes of class X students at SMA 14 Padang City. This research method uses experimental research with a Nonequivalent Control-Group Design research design . The population in this study were all students in class X Science at SMA 14 Padang City, consisting of 5 classes in the even semester of the 2020/2021 academic year. The sampling technique was carried out using the purposive sampling method . The research instrument is a multiple choice test that has been tested for validity, reliability, question discrimination and a good difficulty index. Data were analyzed using the n-gain test and hypothesis testing with the independent sample t-test . The results of data analysis show that the experimental class has a higher n-gain compared to the control class in the medium category. Apart from that, the results of the hypothesis test show a significance value (sig) of less than 0.05, so H 1 is accepted and H 0 is rejected. From the results of this data analysis, it can be concluded that the use of interactive Powerpoint learning media on chemical bond material is effective in improving high school/MA student learning outcomes.